A method for preparing coated essential oils having high temperature resistance and water dispersibility
Patent Information
- Application Number
- CN202610879226.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-17
- Publication Date
- 2026-10-13
AI Technical Summary
[0004]然而,以疏水性高分子材料为壁材的包被产品,虽能耐受饲料制粒的高温,但其疏水性强,产品遇水后分散性差,在动物饮水中易漂浮、结团,且释放速度缓慢;以亲水性高分子材料为壁材的包被产品,虽具有良好的水分散性,但在高温制粒条件下壁材易软化、破裂,精油保留率显著下降;以无机材料为壁材的包被产品,虽然可以提高一定程度的耐高温效果和改善存储过程中的损失,但提高幅度和改善程度均有限,而且进一步将无机材料与胶质、糖类直接混合造粒后,在水中的分散效果也不能尽如人意
[0035]本申请提供了一种具有耐高温性和水分散性的包被精油的制备方法,先利用金属化合物对纳米二氧化硅颗粒改性,与精油混合形成油固相乳化前驱体,再与水相在高速剪切设备中混合,形成初级Pickering乳液,之后再用酪蛋白酸钠和低聚木糖进行二次乳化,形成多层包覆结构,高温造粒后对精油的包埋率可达到85%以上,优选地90%以上。无机二氧化硅颗粒具有较好的热稳定性,在高温制粒时能保持微胶囊的骨架完整性,防止精油因热膨胀而破裂,酪蛋白酸钠和低聚木糖包覆在初级乳液的外层,可以填充在二氧化硅骨架中,在喷雾干燥过程中,随着水分蒸发,能够快速自组装形成尽可能连续、致密的蛋白质膜,包裹在Pickering乳液滴的表面,有效防止精油在高温的条件下的挥发,同时也可以避免氧气渗透,增加稳定性。此外,酪蛋白酸钠具有乳化性,当包被精油遇水后,酪蛋白酸钠迅速水化、溶解,形成稳定的乳液,提高了水中的分散性。
Smart Images

Figure CN122893649A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of essential oil formulation technology, and in particular to a method for preparing coated essential oils with high temperature resistance and water dispersibility. Background Technology
[0002] Plant essential oils are secondary metabolites extracted from plant tissues. They possess highly effective antibacterial, anti-inflammatory, antioxidant, and growth-promoting biological activities, and are increasingly widely used as feed additives in livestock production.
[0003] Plant essential oils face significant stability challenges in practical feed applications due to their volatility, oxidizability, and susceptibility to spoilage, resulting in substantial losses during processing, storage, and transportation. Particularly in the pelleting process of pelleted feed, conditioning and pelleting temperatures typically reach high levels, such as 75-95°C. Under these high temperatures, unprotected active ingredients in plant essential oils undergo significant volatilization and degradation. To address these issues, existing technologies employ microencapsulation techniques using cyclodextrin, ethyl cellulose, starch, and silica to encapsulate essential oils. This significantly reduces the loss rate of effective components during high-temperature pelleting and also minimizes losses during storage and transportation.
[0004] However, while coating products using hydrophobic polymers as wall materials can withstand the high temperatures of feed pelleting, their strong hydrophobicity results in poor dispersibility upon contact with water, causing them to float and clump in animal drinking water, and their release rate is slow. Coating products using hydrophilic polymers as wall materials, while exhibiting good water dispersibility, are prone to softening and cracking under high-temperature pelleting conditions, leading to a significant decrease in essential oil retention. Coating products using inorganic materials as wall materials can improve high-temperature resistance and mitigate losses during storage to some extent, but the improvement is limited. Furthermore, even after directly mixing inorganic materials with colloids and sugars for pelleting, the dispersion effect in water is still unsatisfactory.
[0005] Therefore, there is a need for a method to prepare coated essential oils that takes into account high temperature resistance, long-term storage, and water dispersibility. Summary of the Invention
[0006] The purpose of this application is to provide a method for preparing coated essential oils with high temperature resistance and water dispersibility. By preparing the emulsion stepwise and controlling the conditions in the emulsion preparation process, the structure is stable during the subsequent high-temperature granulation process, which allows for long-term storage and good dispersibility in water.
[0007] A method for preparing a coated essential oil with high temperature resistance and water dispersibility, comprising:
[0008] S100. Modified silica particles are obtained by modifying nano-silica particles with metal compounds.
[0009] S200: The modified silica particles are mixed with essential oil to obtain an emulsified precursor;
[0010] S300. Obtain a first aqueous phase and a second aqueous phase respectively, wherein the first aqueous phase contains an emulsifier and the second aqueous phase contains sodium caseinate and xylooligosaccharide.
[0011] S400. Under the first shear condition, the emulsified precursor obtained in step S200 is mixed with the first aqueous phase to obtain the first emulsion.
[0012] Under the second shear condition, the first emulsion is mixed with the second aqueous phase to obtain the second emulsion;
[0013] S500: The second emulsion is subjected to particle size homogenization treatment and spray drying treatment to obtain the coated essential oil.
[0014] In some embodiments of this application, in S100, at least one of the following conditions is met: condition a) the metal compound includes at least one of ZnO and ZnS; condition b) the mass ratio of the nano-silica particles to the metal compound is 1:(0.05 to 0.15).
[0015] In some embodiments of this application, in S200, the essential oil includes at least one of carvacrol, cinnamaldehyde, thymol, and eugenol; and / or, in S200, the mass ratio of the modified silica particles to the essential oil is 1:(5 to 15).
[0016] In some embodiments of this application, in S300, at least one of the following conditions is met:
[0017] Condition 1) The emulsifier in the first aqueous phase includes at least one of polyglycerol fatty acid ester and polysorbate;
[0018] Condition 2) The preparation method of the second aqueous phase includes: adding sodium caseinate and xylooligosaccharide to water, heating to 50~60℃, adjusting the pH to 6.5 to 7.0 with an acid, and cooling to room temperature for later use;
[0019] Condition 3) The mass ratio of sodium caseinate to xylooligosaccharide is (1.5 to 3):1.
[0020] In some embodiments of this application, in S400, the mass ratio of the emulsifier in the first aqueous phase to the essential oil in the emulsification precursor is (0.02 to 0.1):1;
[0021] The mass ratio of sodium caseinate in the second aqueous phase to the modified silica particles in the emulsion precursor is (10 to 30): 1.
[0022] In some embodiments of this application, in S400, the first shearing condition includes: a first shearing rate V1 of 8000 to 12000 rpm and a first shearing time T1 of 5 to 8 min;
[0023] The second shearing conditions include: a second shearing rate V2 of 6000 to 8000 rpm and a second shearing time T2 of 5 to 10 min.
[0024] In some embodiments of this application, the first shear rate V1 is greater than the second shear rate V2.
[0025] In some embodiments of this application, in S400, the end temperature of the first shearing process is t1, and the end temperature of the second shearing process is t2, satisfying t1 > t2.
[0026] In some embodiments of this application, S500 includes: directly subjecting the second emulsion to particle size uniformization treatment and spray drying treatment to obtain the coated essential oil.
[0027] In some embodiments of this application, S500 includes: adding a crosslinking agent to the second emulsion, performing a crosslinking treatment, followed by particle size homogenization treatment and spray drying treatment to obtain the coated essential oil.
[0028] In some embodiments of this application, the crosslinking agent is selected from any one of transglutaminase, modified starch, chitosan, sodium alginate, and carrageenan.
[0029] In some embodiments of this application, the conditions for the crosslinking treatment include: a crosslinking temperature of 35~45℃ and a crosslinking time of 30~180min.
[0030] In some embodiments of this application, the mass ratio of the crosslinking agent to sodium caseinate in the second aqueous phase is (0.9~1.2):100.
[0031] In some embodiments of this application, in step S500, after the particle size homogenization treatment, the particle size range of the resulting droplets is 0.1~10 μm; and / or,
[0032] The inlet temperature of the spray drying process is 140~200℃;
[0033] The outlet temperature of the spray drying process is 70~100℃.
[0034] The beneficial effects of this application are:
[0035] This application provides a method for preparing coated essential oils with high temperature resistance and water dispersibility. First, nano-silica particles are modified with metal compounds and mixed with essential oils to form an oil-solid phase emulsion precursor. This precursor is then mixed with an aqueous phase in a high-speed shearing apparatus to form a primary Pickering emulsion. A secondary emulsification is then performed using sodium caseinate and xylooligosaccharides to form a multi-layered coating structure. After high-temperature granulation, the encapsulation rate of the essential oil can reach over 85%, preferably over 90%. Inorganic silica particles have good thermal stability, maintaining the integrity of the microcapsule skeleton during high-temperature granulation and preventing the essential oil from rupturing due to thermal expansion. Sodium caseinate and xylooligosaccharides, coating the outer layer of the primary emulsion, can fill the silica skeleton. During spray drying, as water evaporates, they can rapidly self-assemble to form a continuous and dense protein film, encapsulating the surface of the Pickering emulsion droplets. This effectively prevents the volatilization of the essential oil under high-temperature conditions and also avoids oxygen penetration, increasing stability. In addition, sodium caseinate has emulsifying properties. When the coated essential oil comes into contact with water, sodium caseinate quickly hydrates and dissolves to form a stable emulsion, which improves its dispersibility in water.
[0036] The method for preparing coated essential oils provided in this application can effectively improve the high-temperature stability of coated essential oils, especially for coated essential oils that require expansion processing (at a temperature of about 120°C to 140°C).
[0037] Of course, implementing any product or method of this application does not necessarily require achieving all of the advantages described above at the same time. Attached Figure Description
[0038] To more clearly illustrate the technical solutions in the embodiments of this application, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of this application. For those skilled in the art, other embodiments can be obtained based on these accompanying drawings.
[0039] Figure 1 This is a schematic diagram showing the coating essential oil provided in Example 1 of this application dissolving in pure water at 25°C.
[0040] Figure 2 The state of the coated essential oil provided in Example 1 of this application in an aqueous solution as observed under a microscope (1000x);
[0041] Figure 3 This is a SEM image of the nano-ZnO-SiO2 composite particles prepared in Example 1 of this application. Detailed Implementation
[0042] The technical solutions of this application will be clearly and completely described below with reference to the embodiments and accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, and not all embodiments. All other embodiments obtained by those skilled in the art based on this application are within the scope of protection of this application.
[0043] Current essential oil coating preparation methods face the challenge of effectively coating volatile and easily oxidized essential oils, minimizing their loss during storage, and ensuring their water dispersibility during subsequent use.
[0044] This application provides a method for preparing coated essential oils, comprising:
[0045] S100. Modified silica particles are obtained by modifying nano-silica particles with metal compounds.
[0046] S200: Modified silica particles are mixed with essential oils to obtain an emulsified precursor;
[0047] S300. Obtain a first aqueous phase and a second aqueous phase respectively, wherein the first aqueous phase contains an emulsifier and the second aqueous phase contains sodium caseinate and xylooligosaccharide.
[0048] S400: Under the first shear condition, the emulsified precursor obtained in step S200 is mixed with the first aqueous phase to obtain a first emulsion; under the second shear condition, the first emulsion is mixed with the second aqueous phase to obtain a second emulsion.
[0049] S500, the second emulsion is subjected to particle size uniformization treatment and spray drying treatment to obtain coated essential oil.
[0050] This application provides a method for preparing coated essential oils. The method involves a stepwise shearing process to perform inorganic-organic hybrid coating of the essential oil, forming a multi-layered coating. First, hydrophobically modified nano-silica particles are used to coat the essential oil to form a first emulsion. Silica provides a rigid framework and is heat-resistant, effectively preventing the essential oil from escaping due to the rupture of the coating structure during high-temperature granulation and ensuring structural stability during storage. It also inhibits the high-temperature volatilization of the essential oil. The nano-silica particles form a Pickering emulsion interface, ensuring the coated essential oil maintains structural integrity and preventing droplet aggregation when exposed to water. Then, after forming the first emulsion, it is further mixed with a second aqueous phase containing sodium caseinate and xylooligosaccharides. During this process, the caseinate... Sodium caseinate has emulsifying and film-forming properties. It can not only further promote the interfacial bonding between modified silica and essential oils to form a better coating, but also fill the silica framework structure by utilizing its own film-forming properties. During high-temperature granulation, as water evaporates, a continuous and dense shell is formed, sealing the pores as much as possible and effectively preventing the volatilization of essential oils. This is beneficial to the stability of the structure during storage. Furthermore, it can quickly hydrate and dissolve in water during subsequent use. Its emulsifying properties allow the essential oils to be dispersed as evenly as possible in water. Xylooligosaccharides have good water dispersibility and are enriched on the surface of the emulsion droplets during the coating process. During high-temperature granulation and storage, it can effectively prevent the coated essential oil particles from clumping. It also quickly absorbs water and swells upon contact with water, destroying the shell structure and promoting the hydration and dissolution of sodium caseinate, thus causing the shell to disintegrate.
[0051] The first step in this application is to utilize modified nano-SiO2. Nano-SiO2 (containing hydroxyl groups) is hydrophilic and easily wetted by water. After modification, it can be made to exist stably at the oil-water interface. However, due to its own hydrophilicity, it is more easily wetted by the aqueous phase to form an oil-in-water emulsion (O / W). The second step of coating is still carried out in the aqueous phase, using sodium caseinate as an emulsifier. Sodium caseinate is a macromolecular multi-component mixture without a fixed HLB value. Generally, sodium caseinate has stronger hydrophilicity, which is also conducive to the formation of an oil-in-water emulsion (O / W). This application provides an O / W type emulsion.
[0052] In some embodiments of this application, the metal compound includes at least one of ZnO and ZnS. Preferably, the metal compound is ZnO.
[0053] In some embodiments of this application, the method for preparing modified silica particles includes: mixing nano-silica with a Zn salt aqueous solution, then adding a water-soluble carbonate aqueous solution, and positively charged Zn... 2+ CO3 adsorbed on the SiO2 surface 2- With Zn 2+The reaction produces ZnCO3, which, after filtration and calcination, decomposes into ZnO, yielding modified silica. Of course, the preparation method is not limited to the one provided in this application; those skilled in the art can choose a suitable method based on actual needs.
[0054] In some embodiments of this application, during the modification process, the mass ratio of modified silica particles to the metal compound is 1:(0.05~0.15). For example, the mass ratio of modified silica particles to the metal compound can be any value among 1:0.05, 1:0.08, 1:0.1, 1:0.12, 1:0.15, or any two of the above values.
[0055] Of course, the preparation method of modified silica particles in this application is not limited to this, and those skilled in the art can choose other suitable preparation methods as needed.
[0056] This application does not limit the type and state of essential oils; for example, they can be solid or liquid at room temperature, preferably liquid. Essential oils typically have low water solubility and often require spray granulation to improve their dispersibility in water. However, during high-temperature granulation, the inlet temperature of spray drying is often high, such as 140-200°C, and the outlet temperature reaches 70-100°C. If the essential oil is not effectively encapsulated during this spray granulation process, the active ingredients are prone to volatilization, reducing the encapsulation rate.
[0057] In some embodiments of this application, the essential oil in S200 includes at least one of carvacrol, cinnamaldehyde, thymol, and eugenol. Carvacrol, cinnamaldehyde, thymol, and eugenol have attracted widespread attention due to their excellent antibacterial activity and antioxidant stress resistance. When coated essential oils containing carvacrol, cinnamaldehyde, thymol, and eugenol are used in extruded feed, they often need to withstand high temperatures of 120-140°C. Under ultra-high temperature conditions, heat-sensitive components such as essential oils are more likely to volatilize, oxidize, or decompose, thus placing higher demands on the high-temperature stability of coated essential oils. The method for preparing coated essential oils provided in this application effectively improves the high-temperature stability of coated essential oils containing at least one of carvacrol, cinnamaldehyde, thymol, and eugenol, especially under high-temperature conditions of around 140°C.
[0058] In some examples, thymol, carvacrol, cinnamaldehyde, or eugenol can be coated individually. In other examples, multiple essential oils can be coated, for example, by mixing thymol and carvacrol for coating, or by mixing three or four of thymol, carvacrol, cinnamaldehyde, and eugenol for coating. In this application, the component content of the essential oils is not strictly limited when coating multiple essential oils together; those skilled in the art can mix them according to actual needs.
[0059] In some embodiments of this application, in step S200, modified silica and essential oil are mixed and, under high shear, dispersed as uniformly as possible to form an oil-solid suspension. In some examples, the shear rate is 8000~12000 rpm, and the shear time is 0.5~2 min. In some examples, the shear rate can be any value among 8000 rpm, 9000 rpm, 10000 rpm, 11000 rpm, and 12000 rpm, or any two of the above values; in some examples, the shear time can be any value among 0.5 min, 1 min, 1.5 min, and 2 min, or any two of the above values. In this application, the shear conditions satisfying the above ranges not only achieve sufficient mixing of the solid and oil phases, making the solid phase as uniformly dispersed as possible in the oil phase, but also ensure that the temperature does not rise excessively during high-speed shearing, avoiding the volatilization loss of essential oils, and reducing the energy consumption required for shearing.
[0060] In some embodiments of this application, in step S200, the mass ratio of modified silica particles to essential oil is 1:(5 to 15). In some examples, the mass ratio of modified silica particles to essential oil can be any value among 1:5, 1:8, 1:10, 1:12, and 1:15, or any two of the above values. In this application, controlling the mass ratio of modified silica particles to essential oil within the above range can achieve effective coating of essential oil by the modified silica particles, which is beneficial for maintaining the skeleton structure during high-temperature granulation and storage, and will not cause waste of nano-silica particles, which is beneficial for the later release of essential oil.
[0061] In some embodiments of this application, in step S300, a first aqueous phase containing an emulsifier is obtained by uniformly mixing the emulsifier with deionized water. The emulsifier includes at least one of polyglycerol fatty acid esters and polysorbate esters. Adding emulsifiers such as polyglycerol fatty acid esters and polysorbate esters to the first aqueous phase is beneficial for improving the water-oil interface and promoting the binding of modified silica particles with essential oils. In this application, since the modified silica particles have high strength, it is necessary to control the amount of modified silica particles added in order to achieve better release in the later stage. Therefore, an auxiliary emulsifier is added to the first aqueous phase, such as an emulsifier with HLB≥8. By adding an auxiliary emulsifier to the first aqueous phase, the dispersibility of essential oils in the aqueous phase and the uniformity of essential oil particle size during step S400 can be improved, thereby improving the emulsification and coating effect of modified silica particles on essential oils. Polyglycerol fatty acid esters can be hexaglycerol monooleate, decaglycerol stearate, decaglycerol monolaurate, etc.; polysorbate esters can be Tween-60, Tween-80, etc.
[0062] In some embodiments of this application, in step S300, a second aqueous phase containing sodium caseinate and xylooligosaccharides is obtained. The method for preparing the second aqueous phase in this application includes: adding sodium caseinate and xylooligosaccharides to water, heating to 50-60°C, adjusting the pH to 6.5-7.0 with an acid, and cooling to room temperature for later use. In some examples, the heating temperature can be any value among 50°C, 52°C, 54°C, 56°C, 58°C, and 60°C, or any two of the above values; in some examples, the pH is adjusted to any value among 6.5, 6.6, 6.7, 6.8, 6.9, and 7.0, or any two of the above values. In some examples, the acid can be citric acid, lactic acid, malic acid, sorbic acid, etc. In this application, the type of acid is not strictly limited; those skilled in the art can select it according to actual needs.
[0063] In this application, sodium caseinate can fill the gaps between hydrophobically modified nano-silica particles, forming a physical barrier that effectively prevents the volatilization of essential oils and oxygen penetration. Furthermore, this protein film has good mechanical strength and flexibility, and can resist thermal stress and mechanical shear force during feed pelleting, protecting the internal essential oils. On the other hand, when the coated essential oils come into contact with water, sodium caseinate quickly hydrates and dissolves, allowing the essential oils to disperse rapidly and evenly in the water, forming a stable emulsion.
[0064] In this application, the outer wall material also contains xylooligosaccharides. Xylooligosaccharide molecules contain numerous hydroxyl groups (-OH), which rapidly form hydrogen bonds with water molecules upon contact with water, resulting in strong hydration. During the preparation of the coated essential oil, the second aqueous phase is added to the system during the second shearing process, placing sodium caseinate and xylooligosaccharides in a post-coating state. The two form a mixed matrix outer membrane. During spray drying, due to the stronger interaction between xylooligosaccharides and water, and the fact that xylooligosaccharides are small-molecule sugars while sodium caseinate is a large-molecule protein, smaller molecules typically diffuse faster. As water evaporates, xylooligosaccharides more readily occupy the membrane surface, meaning they form a blended membrane with caseinate. Xylooligosaccharides tend to accumulate on the outer surface of the microcapsules. Utilizing this property, when the coated essential oil powder is immersed in water, the surface xylooligosaccharides instantly absorb water, causing the powder to change from a hydrophobic to a hydrophilic state, resulting in rapid wetting and settling. In this application, the degree of polymerization of the xylooligosaccharides is 2 to 7, such as xylobiose and xylotriose.
[0065] In some embodiments of this application, in step S300, the mass ratio of sodium caseinate to xylooligosaccharides is (1.5 to 3):1. In some examples, the mass ratio of sodium caseinate to xylooligosaccharides is any value among 1.5:1, 1.8:1, 2:1, 2.5:1, and 3:1, or any two of the above values. In this application, by controlling the mass ratio of sodium caseinate to xylooligosaccharides within the above range, both good coating effect and rapid water solubility and dispersion effect after contact with water can be achieved.
[0066] In some embodiments of this application, in step S400, under a first shear condition, the emulsified precursor obtained in step S200 is mixed with a first aqueous phase to obtain a first emulsion; under a second shear condition, the first emulsion is mixed with a second aqueous phase to obtain a second emulsion. In this application, the essential oil is subjected to inorganic and organic high-speed shear treatment in steps. First, the emulsified precursor containing modified silica and essential oil is mixed with the first aqueous phase. Under the action of high-speed shear force, the nano-silica is adsorbed at the water-oil interface, forming a highly stable protective layer around the essential oil particles. Then, a second aqueous phase containing sodium caseinate and xylooligosaccharides is added. Because sodium caseinate has good amphiphilicity, it is adsorbed at the oil-water interface under the action of high-speed shear force, forming a coating on the modified silica and essential oil. Then, during the spray drying process, as the water evaporates, it self-assembles to form a protein film that is as continuous and dense as possible. And xylooligosaccharides, due to their hydrophilicity, are more easily enriched in the outer layer during the spray drying process.
[0067] Therefore, this application employs a stepwise high-speed shearing process to first form an inorganic protective layer, followed by organic membrane coating. On one hand, silica provides a rigid framework, while sodium caseinate forms a dense outer membrane. This dual protection improves the high-temperature performance of the coated essential oil and reduces the risk of essential oil leakage / evaporation due to structural breakage. It also prevents problems such as moisture absorption, oxidation, and essential oil seepage, thus improving the stability of the coated essential oil during storage and transportation. On the other hand, by coating sodium caseinate and xylooligosaccharides later, placing them as far as possible on the outer layer, it not only achieves a sealing effect but also allows the coated essential oil to be rapidly wetted by xylooligosaccharides upon contact with water, causing rapid volume expansion and swelling pressure. This expands the wall structure of the microcapsule from the inside, exposing more sodium caseinate to the water and utilizing its emulsifying properties to ensure rapid and uniform dispersion of the essential oil in water, forming a stable emulsion.
[0068] In some embodiments of this application, in step S400, the mass ratio of emulsifier in the first aqueous phase to essential oil in the emulsion precursor is (0.02 to 0.1):1. In some examples, the mass ratio of emulsifier to essential oil is any value among 0.02:1, 0.04:1, 0.06:1, 0.08:1, and 0.1:1, or any two of the above values. In this application, by controlling the mass ratio of emulsifier in the first aqueous phase to essential oil in the emulsion precursor within the above range, it is beneficial to improve the uniformity of droplet size in the first emulsion.
[0069] In some embodiments of this application, in step S400, the mass ratio of sodium caseinate in the second aqueous phase to modified silica particles in the emulsion precursor is (10 to 30):1. In some examples, the mass ratio of sodium caseinate to modified silica particles can be any value among 10:1, 15:1, 20:1, 25:1, and 30:1, or any two of the above values. In this application, by controlling the mass ratio of sodium caseinate in the second aqueous phase to modified silica particles in the emulsion precursor within the above range, a protein membrane with better coating effect can be achieved.
[0070] In some embodiments of this application, in step S400, the first shearing conditions include: a first shear rate V1 of 8000 to 12000 rpm and a first shearing time T1 of 5 min to 8 min; the second shearing conditions include: a second shear rate V2 of 6000 to 8000 rpm and a second shearing time T2 of 5 min to 10 min. In this application, essential oils have a certain degree of volatility, especially increasing with rising temperature. During the preparation of emulsion droplets, if a consistently high shear rate is maintained, the temperature of the essential oil can easily rise, accelerating its volatilization and resulting in a waste of active ingredients. In this application, by controlling the stepwise shearing process, a higher shear rate is required in the first shearing process to form a well-dispersed Pickering emulsion. Therefore, the shearing rate is controlled at 8000 to 12000 rpm and the shearing time is controlled at 5 to 8 min. In the second shearing process, which is mainly for forming a coating film, the shearing rate can be appropriately reduced, for example, the shearing rate can be controlled at 6000 to 8000 rpm. This can reduce the temperature of the system, minimize the volatilization of active substances and essential oils, and improve the encapsulation rate.
[0071] In some embodiments of this application, during the first shearing process, the first shearing rate V1 can be any value among 8000 rpm, 9000 rpm, 10000 rpm, 11000 rpm, and 12000 rpm, or any two of the above values; the first shearing time T1 can be any value among 5 min, 6 min, 7 min, and 8 min, or any two of the above values; during the second shearing process, the second shearing rate V2 can be any value among 6000 rpm, 7000 rpm, and 8000 rpm, or any two of the above values; the second shearing time T2 can be any value among 5 min, 6 min, 7 min, 8 min, 9 min, and 10 min, or any two of the above values.
[0072] In some embodiments of this application, the first shear rate V1 is greater than the second shear rate V2. In this application, since a small and uniformly distributed emulsion can be formed through two high-speed shearing processes during the emulsion precursor preparation stage and the first shearing process, the shear rate in the second shearing process can be appropriately reduced, thereby lowering the system temperature and effectively preventing the volatilization of essential oils.
[0073] In this application, the equipment for high-speed shearing is not strictly limited. For example, the high-speed shearing equipment can be a high-speed shearing machine, an emulsion pump, a colloid mill, etc.
[0074] In some embodiments of this application, in step S400, the highest temperature in the first shearing process is t1, and the highest temperature in the second shearing process is t2, satisfying t1 > t2. In this application, the first shearing process includes: under a first shearing condition, mixing the emulsified precursor obtained in step S200 with a first aqueous phase to obtain a first emulsion; the second shearing process includes: under a second shearing condition, mixing the first emulsion with a second aqueous phase to obtain a second emulsion. Since the second shear rate V2 is less than the first shear rate V1, it can promote system cooling.
[0075] In some embodiments of this application, S500 includes: directly subjecting the second emulsion to particle size homogenization treatment and spray drying treatment to obtain coated essential oil; in other embodiments of this application, S500 includes: adding a crosslinking agent to the second emulsion, performing crosslinking treatment, and then performing particle size homogenization treatment and spray drying treatment to obtain coated essential oil.
[0076] In some embodiments of this application, in step S500, the crosslinking agent is selected from any one of transglutaminase, modified starch, chitosan, sodium alginate, and carrageenan. In this application, by adding a crosslinking agent to the second emulsion, sodium caseinate can be crosslinked, which not only constructs a stable three-dimensional network but also improves the stability of the emulsion, thereby ensuring the formation of a more stable and dense organic protective layer at high temperatures, especially under harsh high-temperature conditions of around 140°C. Furthermore, it can improve the storage performance of the coated essential oil. The crosslinking agent in this application refers to a substance that connects molecular chains into a network structure, including chemical crosslinking and physical crosslinking. In some preferred examples, the crosslinking agent is transglutaminase, and the chemical crosslinking between transglutaminase and sodium caseinate results in a more stable gel network structure.
[0077] In some embodiments of this application, in step S500, the crosslinking treatment conditions include: a crosslinking temperature of 35~45℃, a crosslinking time of 30~180min, and a mass ratio of the crosslinking agent to sodium caseinate in the second aqueous phase of (0.9~1.2):100. In some examples, the crosslinking temperature can be any value among 35℃, 38℃, 40℃, 42℃, and 45℃, or any two of the above values; the crosslinking time can be any value among 30min, 50min, 70min, 90min, 110min, 130min, 150min, 160min, and 180min, or any two of the above values; and the mass ratio of the crosslinking agent to sodium caseinate in the second aqueous phase can be any value among 0.9:100, 1.0:100, 1.1:100, and 1.2:100, or any two of the above values. By controlling the cross-linking treatment conditions and the amount of cross-linking agent added, the cross-linking treatment can be more thorough, the resulting network structure is more stable, and the volatilization of essential oils can be avoided. In addition, a moderate degree of cross-linking is also beneficial to the subsequent release of essential oils.
[0078] In some embodiments of this application, after the particle size homogenization treatment in step S500, the particle size range of the resulting emulsion droplets is 0.1~10μm. The homogenization treatment in this application can be performed in a high-pressure homogenizer at a pressure of, for example, 50~80MPa, for 3-5 cycles to obtain a stable emulsion with fine and uniform particle size distribution. In some examples, the particle size range of the emulsion droplets can be any value among 0.1μm, 0.5μm, 1μm, 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, and 10μm, or any two of the above values.
[0079] In some embodiments of this application, in step S500, the homogenized droplets are subjected to spray drying. The inlet temperature of the spray drying process is 140-200°C, and the outlet temperature is 70-100°C. Preferably, the inlet temperature is 160-180°C, and the outlet temperature is 80-90°C. In some examples, the inlet temperature can be any value among 140°C, 150°C, 160°C, 170°C, 180°C, 190°C, and 200°C, or any two of the above values; the outlet temperature can be any value among 70°C, 80°C, 90°C, and 100°C, or any two of the above values.
[0080] Example
[0081] The embodiments and comparative examples provided below illustrate the implementation of this application in more detail. Various tests and evaluations were conducted according to the methods described below. Furthermore, unless otherwise specified, "parts" and "%" are quality standards.
[0082] Raw material description:
[0083] All raw materials used in the embodiments of this application can be obtained commercially.
[0084] Test method:
[0085] The content of essential oils was determined by ultraviolet spectrophotometry (UV-Vis), gas chromatography (GC), or high performance liquid chromatography.
[0086] Encapsulation rate = (total essential oil mass - surface essential oil mass) / theoretical total mass of added essential oil × 100%.
[0087] Total essential oil mass: The sum of all essential oils inside and on the surface of the coated essential oil.
[0088] Surface essential oil quality: Essential oils that exist only on the surface of the coated essential oil and are not covered by the wall material.
[0089] Test method for total essential oil quality: Prepare a mixed solvent containing n-hexane and petroleum ether, and then perform ultrasonic disruption for 30 minutes, followed by Soxhlet extraction for 6 hours to break up the coated essential oil and completely release the essential oil;
[0090] Test method for surface essential oil quality: Add the coated essential oil to petroleum ether, vortex wash at room temperature for 2 minutes, centrifuge and take the supernatant.
[0091] Example 1: Preparation of modified silica particles
[0092] At room temperature (25℃), 10g of nano-silica (particle size 50±5nm) was weighed and dispersed in 500ml of water. Then, 2.3g of Zn(NO3)2 (concentration 0.01mol / L, added slowly in aqueous solution at a dropping rate of 100ml / h) was added. After that, 1.3g of Na2CO3 (concentration 0.01mol / L, added slowly in aqueous solution at a dropping rate of 50ml / h) was added. After the reaction was completed, the mixture was aged for 10h, filtered, washed, and then calcined at 480℃ for 3.5h to obtain ZnO-SiO2 composite particles, wherein the mass ratio of nano-SiO2 to ZnO was 1:0.1.
[0093] Example 2: Preparation of modified silica particles
[0094] At room temperature (25℃), 10g of nano-silica (particle size 50±5nm) was weighed and dispersed in 500ml of water. Then, 3.5g of Zn(NO3)2 (concentration 0.01mol / L, added slowly in aqueous solution at a dropping rate of 100ml / h) was added. After that, 2g of Na2CO3 (concentration 0.01mol / L, added slowly in aqueous solution at a dropping rate of 50ml / h) was added. After the reaction was completed, the mixture was aged for 10h, filtered, washed, and then calcined at 420℃ for 4h to obtain ZnO-SiO2 composite particles, wherein the mass ratio of nano-SiO2 to ZnO was 1:0.15.
[0095] Example 1
[0096] a) Preparation of emulsified precursors
[0097] Take 10.0g of essential oil (carvacrol), add 2.0g of the modified nano ZnO-SiO2 composite particles prepared in Example 1 above, and shear disperse at 8000rpm for 2min to make the composite particles uniformly dispersed in the essential oil to form an oil phase suspension, i.e., emulsified precursor.
[0098] b) First aqueous phase configuration
[0099] Take 150 mL of deionized water, add decaglycerol stearate at 4% of the essential oil mass, and stir to disperse it evenly to obtain the first aqueous phase;
[0100] c) Second aqueous phase configuration
[0101] Take 22.0 g of sodium caseinate and 12.0 g of xylooligosaccharide, add them to 300 mL of deionized water, stir and heat to 55°C to completely dissolve them, adjust the pH to 6.8 with citric acid, cool to room temperature and set aside to obtain the second aqueous phase;
[0102] d) Preparation of emulsion
[0103] Under high-speed shearing conditions of 10,000 rpm, the obtained emulsified precursor was mixed with the first aqueous phase. Decaglycerol stearate was used as an auxiliary emulsifier and adsorbed at the oil-water interface to prevent oil droplet aggregation. Shearing was performed for 6 minutes to obtain the first emulsion. The end temperature t1 of the first shearing process was 45℃. Then, the shearing rate was adjusted to 7,000 rpm, and the second aqueous phase was slowly added to the first emulsion. Shearing was continued for 10 minutes to allow sodium caseinate to be fully adsorbed on the surface of the oil droplets in the first emulsion to form a continuous outer shell layer. The end temperature t2 of the second shearing process was 37℃. After shearing, a stable emulsion was obtained, and the droplet size was controlled within the range of 2~6 μm.
[0104] e) Particle size homogenization treatment
[0105] The emulsion obtained in the above steps was transferred to a high-pressure homogenizer and homogenized twice at a pressure of 35 MPa to further refine the droplet size to 1~5 μm, resulting in a uniform fine emulsion.
[0106] f) Spray drying process
[0107] The inlet air temperature of the spray dryer was set to 170℃, the outlet air temperature to 80℃, the atomization pressure to 0.4MPa, and the feed rate to 12 mL / min. The resulting fine emulsion was fed into a spray drying tower under continuous stirring for drying. The powder collected from the bottom of the tower and the cyclone separator was passed through an 80-mesh sieve to obtain coated essential oil powder. The encapsulation rate of the coated essential oil was 91.5%.
[0108] Example 2
[0109] a) Preparation of emulsified precursors
[0110] Take 10.0 g of essential oil (cinnamaldehyde), add 1.0 g of the modified nano ZnO-SiO2 composite particles prepared in Example 1 above, and disperse them at high speed at 12000 rpm for 0.5 min to make the composite particles uniformly dispersed in the essential oil to form an oil phase suspension, i.e., the emulsion precursor.
[0111] b) First aqueous phase configuration
[0112] Take 150 mL of deionized water, add decaglycerol stearate at 8% of the essential oil mass, and stir to disperse it evenly to obtain the first aqueous phase;
[0113] c) Second aqueous phase configuration
[0114] Take 20.0 g of sodium caseinate and 10.0 g of xylooligosaccharide, add them to 300 mL of deionized water, stir and heat to 60 °C to completely dissolve them, adjust the pH to 7 with citric acid, cool to room temperature and set aside to obtain the second aqueous phase;
[0115] d) Preparation of emulsion
[0116] Under high-speed shearing conditions of 12000 rpm, the obtained emulsified precursor was mixed with the first aqueous phase. Decaglycerol stearate was used as an auxiliary emulsifier and adsorbed at the oil-water interface to prevent oil droplet aggregation. Shearing was performed for 5 min to obtain the first emulsion. The end temperature t1 of the first shearing process was 47℃. Then, the shearing rate was adjusted to 8000 rpm, and the second aqueous phase was slowly added to the first emulsion. Shearing was continued for 8 min to allow sodium caseinate to be fully adsorbed on the surface of the oil droplets in the first emulsion, forming a continuous outer shell layer. The end temperature t2 of the second shearing process was 39℃. After shearing, a stable emulsion was obtained, and the droplet size was controlled within the range of 1~5 μm.
[0117] e) Particle size homogenization treatment
[0118] The emulsion obtained in the above steps was transferred to a high-pressure homogenizer and homogenized twice at a pressure of 35 MPa to further refine the droplet size to 0.5~4 μm, resulting in a uniform and fine emulsion.
[0119] f) Spray drying process
[0120] The inlet air temperature of the spray dryer was set to 150℃, the outlet air temperature to 75℃, the atomization pressure to 0.5MPa, and the feed rate to 10 mL / min. The resulting fine emulsion was fed into a spray drying tower under continuous stirring for drying. The powder collected from the bottom of the tower and the cyclone separator was passed through an 80-mesh sieve to obtain coated essential oil powder. The encapsulation rate of the coated essential oil was 90.6%.
[0121] Example 3
[0122] a) Preparation of emulsified precursors
[0123] Take 10.0 g of essential oil (thymol), add 0.7 g of the modified nano ZnO-SiO2 composite particles prepared in Example 2 above, and shear disperse at high speed at 11000 rpm for 1 min to make the composite particles uniformly dispersed in the essential oil to form an oil phase suspension, i.e., emulsified precursor.
[0124] b) First aqueous phase configuration
[0125] Take 150 mL of deionized water, add decaglycerol stearate equivalent to 10% of the essential oil mass, stir to disperse it evenly, and obtain the first aqueous phase;
[0126] c) Second aqueous phase configuration
[0127] Take 21.0 g of sodium caseinate and 7.0 g of xylooligosaccharide, add them to 300 mL of deionized water, stir and heat to 50°C to completely dissolve them, adjust the pH to 6.5 with citric acid, cool to room temperature and set aside to obtain the second aqueous phase;
[0128] d) Preparation of emulsion
[0129] Under high-speed shearing conditions of 8000 rpm, the obtained emulsified precursor was mixed with the first aqueous phase. Decaglycerol stearate was used as an auxiliary emulsifier and adsorbed at the oil-water interface to prevent oil droplet aggregation. Shearing was performed for 8 minutes to obtain the first emulsion. The end temperature t1 of the first shearing process was 42℃. Then, the shearing rate was adjusted to 6000 rpm, and the second aqueous phase was slowly added to the first emulsion. Shearing was continued for 10 minutes to allow sodium caseinate to be fully adsorbed on the surface of the oil droplets in the first emulsion, forming a continuous outer shell layer. The end temperature t2 of the second shearing process was 36℃. After shearing, a stable emulsion was obtained, and the droplet size was controlled within the range of 3~7μm.
[0130] e) Particle size homogenization treatment
[0131] The emulsion obtained in the above steps was transferred to a high-pressure homogenizer and homogenized twice at a pressure of 35 MPa to further refine the droplet size to 2-6 μm, resulting in a uniform and fine emulsion.
[0132] f) Spray drying process
[0133] The inlet air temperature of the spray dryer was set to 180℃, the outlet air temperature to 82℃, the atomization pressure to 0.6MPa, and the feed rate to 12 mL / min. The resulting fine emulsion was fed into a spray drying tower under continuous stirring for drying. The powder collected from the bottom of the tower and the cyclone separator was passed through an 80-mesh sieve to obtain coated essential oil powder. The encapsulation rate of the coated essential oil was 91.1%.
[0134] Example 4
[0135] The difference from Example 1 is that the shear rate of the second shearing process was adjusted to 10,000 rpm, meaning the first and second shear rates were the same, and the end temperature t2 of the second shearing process was approximately 47°C. The encapsulation rate of the coated essential oil was 87.1%.
[0136] Comparing Example 4 with Example 1, it can be seen that lowering the shear rate in the second shearing process in Example 1 can improve the encapsulation effect of the essential oil. This is because in Example 4, the overall temperature of the second shearing process is relatively high, around 47°C, and is accompanied by strong shearing action, resulting in a certain amount of loss of active components.
[0137] Example 5
[0138] The difference from Example 1 is that the emulsion obtained in step d) is mixed with a crosslinking agent before homogenization. Specifically:
[0139] The emulsion obtained in step d) was mixed with transglutaminase at an amount of 1 wt% of sodium caseinate. The mixture was cross-linked at 37°C for 60 min to obtain a cross-linked emulsion. The cross-linked emulsion was then subjected to particle size homogenization and spray drying to obtain the coated essential oil. The encapsulation rate of the coated essential oil was 91.8%.
[0140] By comparing Example 5 with Example 1, it can be seen that the coated essential oil still has a good encapsulation rate after adding transglutaminase.
[0141] Comparative Example 1
[0142] The difference from Example 1 is that 150 mL of deionized water was directly used as the first aqueous phase and mixed with the emulsification precursor. The encapsulation rate of the coated essential oil was 81.4%.
[0143] By comparing Example 1 and Comparative Example 1, it can be seen that the absence of decaglycerol stearate as an auxiliary emulsifier in the first aqueous phase has a significant impact on the encapsulation efficiency. This is because decaglycerol stearate has the effect of improving the interfacial effect, which is beneficial to promoting the emulsification of modified silica particles. In the water-oil phase containing only modified silica particles, the emulsification effect of the first emulsion is weak. In the subsequent high-temperature granulation process, more essential oils evaporate, reducing the encapsulation efficiency.
[0144] Comparative Example 2
[0145] The difference from Example 1 is that: d) stepwise shearing is not performed during the emulsion preparation stage, as detailed below:
[0146] d) Under high-speed shearing conditions of 10,000 rpm, the emulsified precursor obtained in step a) was directly mixed with the first aqueous phase obtained in step b) and the second aqueous phase obtained in step c), and sheared for 16 min. The shearing end temperature was approximately 47°C. The encapsulation rate of the coated essential oil was 76.4%.
[0147] By comparing Example 1 and Comparative Example 2, it can be seen that in the emulsion preparation stage, directly mixing the emulsifying precursor with the first aqueous phase and the second aqueous phase is not conducive to the formation of a multilayer structure. The subsequent high-temperature granulation leads to the loss of essential oils, resulting in an encapsulation rate of only 76.4%.
[0148] High-Temperature Stability and Storage Performance Test Examples
[0149] Stability and storage performance tests were conducted on Examples 1 to 5, as well as Comparative Examples 1 and 2, under different simulated temperature and time conditions.
[0150] Simulated temperature and time conditions 1: Temperature 85℃, humidity 50%, processing time 30min;
[0151] Simulated temperature and time conditions 2: Temperature 85℃, humidity 80%, processing time 30min;
[0152] Simulated temperature and time conditions 3: Temperature 140℃, humidity 50%, processing time 10min;
[0153] Simulated temperature and time conditions 4: Temperature 50℃, humidity 50%, processing time 60 days;
[0154] Simulated temperature and time conditions 5: Temperature 25℃, humidity 50%, treatment time 1 year;
[0155] Table 1. Essential oil retention rate under different temperature and time conditions.
[0156] Example 1 99.9% 99.9% 97.9% 99.3% 99.0% Example 2 99.9% 98.6% 96.7% 99.1% 97.4% Example 3 99.9% 99.9% 98.1% 99.4% 98.7% Example 4 96.8% 94.1% 90.8% 96.5% 93.2% Example 5 99.9% 99.9% 99.1% 99.9% 99.8% Comparative Example 1 90.1% 84.6% 77.9% 88.9% 86.2% Comparative Example 2 82.9% 72.7% 60.7% 79.1% 77.6%
[0157] As can be seen from Table 1:
[0158] 1. In Examples 1 to 5, the coated essential oils prepared by the method provided in this application have good stability at high temperatures. In particular, when the simulated temperature rises to 140°C, they still have a good retention rate of over 90%. Among them, Examples 1 to 3 can reach over 95%, and Example 5 can reach over 99%.
[0159] 2. As can be seen from Example 5, when the cross-linking agent transglutaminase is added, not only can excellent high-temperature performance be obtained, especially the retention rate is still high under high temperature conditions of 140°C, but storage performance can also be significantly improved.
[0160] 3. As can be seen from Example 4, when the first shear rate and the second shear rate are the same, it will have a certain impact on the high-temperature performance. It is speculated that this may be because the overall high-speed shearing time is too long, the overall system temperature is too high, which is not conducive to the emulsification and coating process.
[0161] 4. By comparing Comparative Example 1 with Example 1, it can be seen that when the first aqueous phase does not contain auxiliary emulsifier, it has a greater impact on high-temperature performance and storage performance. This is because when only nano-silica particles are used as emulsifier, the amount of emulsifier added is small, the emulsification effect is poor, the skeleton structure is unstable, and the essential oil is easy to volatilize under high temperature environment.
[0162] 5. A comparison between Comparative Example 2 and Example 1 shows that directly mixing the emulsion precursor with the first and second aqueous phases during the emulsion preparation stage has a significant impact on high-temperature and storage performance, especially under simulated high-temperature conditions of 140°C. This is because direct mixing cannot effectively form an inorganic-organic protective structure, leading to a decrease in high-temperature and storage performance.
[0163] Aqueous solution test
[0164] Test method: At room temperature, the coated essential oil obtained in Example 1 was dissolved in water at a ratio of 1g / 100ml. See the photograph of the dissolved product. Figure 1 As shown.
[0165] from Figure 1 It can be seen that the coated essential oil disperses well in water, resulting in a uniform emulsion without clumping, settling, or floating oil.
[0166] The aqueous solution was observed under a 1000x microscope, as follows: Figure 2 As shown, the essential oil particles are evenly dispersed in water without clumping or aggregation, and the particle size uniformity is also good.
[0167] The coated essential oils obtained in other embodiments also have similar water dispersibility effects as in Example 1, which will not be described in detail here.
[0168] It should be noted that, in this document, relational terms such as "first" and "second" are used only to distinguish one entity or operation from another, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Furthermore, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, or article that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, or article.
[0169] The above description is only a preferred embodiment of this application and is not intended to limit this application. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this application should be included within the scope of protection of this application.
Claims
1. A method for preparing a coated essential oil with high temperature resistance and water dispersibility, characterized in that, include: S100. Modified silica particles are obtained by modifying nano-silica particles with metal compounds. S200: The modified silica particles are mixed with essential oil to obtain an emulsified precursor; S300. Obtain a first aqueous phase and a second aqueous phase respectively, wherein the first aqueous phase contains an emulsifier and the second aqueous phase contains sodium caseinate and xylooligosaccharide. S400. Under the first shear condition, the emulsified precursor obtained in step S200 is mixed with the first aqueous phase to obtain the first emulsion. Under the second shear condition, the first emulsion is mixed with the second aqueous phase to obtain the second emulsion; S500, the second emulsion is subjected to at least particle size uniformization treatment and spray drying treatment to obtain the coated essential oil.
2. The preparation method according to claim 1, characterized in that, In S100, at least one of the following conditions is met: Condition a) The metal compound includes at least one of ZnO and ZnS; Condition b) The mass ratio of the nano-silica particles to the metal compound is 1:(0.05 to 0.15).
3. The preparation method according to claim 1, characterized in that, In S200, the essential oil includes at least one of carvacrol, cinnamaldehyde, thymol, and eugenol; and / or, In S200, the mass ratio of the modified silica particles to the essential oil is 1:(5 to 15).
4. The preparation method according to claim 1, characterized in that, In S300, at least one of the following conditions is met: Condition 1) The emulsifier in the first aqueous phase includes at least one of polyglycerol fatty acid ester and polysorbate; Condition 2) The preparation method of the second aqueous phase includes: adding sodium caseinate and xylooligosaccharide to water, heating to 50~60℃, adjusting the pH to 6.5 to 7.0 with an acid, and cooling to room temperature for later use; Condition 3) The mass ratio of sodium caseinate to xylooligosaccharide is (1.5 to 3):
1.
5. The preparation method according to claim 1, characterized in that, In S400, the mass ratio of the emulsifier in the first aqueous phase to the essential oil in the emulsified precursor is (0.02 to 0.1):1; The mass ratio of sodium caseinate in the second aqueous phase to the modified silica particles in the emulsion precursor is (10 to 30):
1.
6. The preparation method according to claim 1, characterized in that, In S400, the first shearing conditions include: a first shearing rate V1 of 8000 to 12000 rpm and a first shearing time T1 of 5 min to 8 min; The second shearing conditions include: a second shearing rate V2 of 6000 to 8000 rpm and a second shearing time T2 of 5 min to 10 min.
7. The preparation method according to claim 6, characterized in that, The first shear rate V1 is greater than the second shear rate V2.
8. The preparation method according to claim 1, characterized in that, In S400, the end temperature of the first shearing process is t1, and the end temperature of the second shearing process is t2, satisfying: t1 > t2.
9. The preparation method according to claim 1, characterized in that, S500 includes: directly subjecting the second emulsion to particle size uniformization treatment and spray drying treatment to obtain the coated essential oil; or... S500 includes: adding a crosslinking agent to the second emulsion, performing crosslinking treatment, followed by particle size homogenization treatment and spray drying treatment to obtain the coated essential oil; Preferably, the crosslinking agent is selected from any one of transglutaminase, modified starch, chitosan, sodium alginate, and carrageenan; The conditions for the crosslinking treatment include: crosslinking temperature of 35~45℃ and crosslinking time of 30~180min.
10. The preparation method according to claim 1, characterized in that, In S500, after the particle size homogenization treatment, the resulting droplets have a particle size range of 0.1~10μm; and / or, The inlet temperature of the spray drying process is 140~200℃; The outlet temperature of the spray drying process is 70~100℃.